'Cooking is for everyone?': Exploring the complexity of gendered dynamics in a cookstove intervention study in rural Malawi. Issue 1 (6th December 2021) - Ardrey, Jane; Jehan, Kate; Desmond, Nicola; Kumbuyo, Caroline; Mortimer, Kevin; Tolhurst, Rachel
ABSTRACT: Background: Household air pollution (HAP) resulting from cooking on open fires has been linked to considerable ill-health in women and girls, including chronic respiratory diseases, and has been identified as a contributor to climate change. It has been suggested that cleaner burning cookstoves can mitigate these risks, and that time saved through speedier cooking can lead to the economic empowerment of women. Despite these and other potential advantages of cookstoves, sustained use is difficult to achieve. Objective: We used qualitative methods (focus groups, interviews, observation) and the participatory methodology Photovoice in order to inform a deeper understanding of gendered social relationships within the Cooking and Pneumonia Study (CAPS) in rural Malawi. Methods: Over five CAPS villages, forty women and ten men were recruited for Photovoice activities, including image collection, village-level focus group discussion and interviews. Data were also collected from interviews with village-based community representatives. Results: This study facilitated a rich exploration of context-specific gendered household roles and power relations which found that there was space for contestation in seemingly entrenched and 'traditional' household responsibilities. The results suggest that the introduction of cookstoves through CAPS provided a focus for this contestation. It was evident that men and children also cooked, and that cooking played a central role in the gendered socialisation of children. However, there were no indications that time saved resulted in the empowerment of women. Conclusion: Our findings suggest that dominant narratives of the links between gender and cookstoves are often reductive and fail to reflect the complexity of gender power relations. The use of qualitative methods incorporating Photovoice helped to facilitate an alternative 'bottom-up' view of cookstove use which demonstrated that while cookstoves may disrupt gendered relationships in target communities, positive impacts for women and girls cannot be assumed.